2020
DOI: 10.1002/ange.202010316
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Inhibition of the SARS‐CoV‐2 Main Protease: Insights from Mass Spectrometry Based Assays**

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…El-Baba et al, in their mass spectrometry based study for the investigation of allosteric inhibitor of M pro revealed binding of potential allosteric inhibitor x1187 at the binding site comprising residues Phe8, Met6, Gln127, Ser139, Asp295, Arg298, and Gln299. Gln127 being common to the mentioned studies and to our analysis may be considered as effective residue for allosteric inhibition thus depicting the accuracy of allosteric site selection in the present study (El-Baba et al 2020 ). Iftikhar et al in their in-silico study on inhibitors against three potential enzyme targets of SARS-CoV-2 reported Bagrosin as an allosteric inhibitor, binding with an energy of − 7.9 kcal/mol at an allosteric site lying close to the site reported in the present study, of SARS-CoV-2 proteinase with Lys5 as common interacting residue (Iftikhar et al 2020 ).…”
Section: Resultsmentioning
confidence: 67%
“…El-Baba et al, in their mass spectrometry based study for the investigation of allosteric inhibitor of M pro revealed binding of potential allosteric inhibitor x1187 at the binding site comprising residues Phe8, Met6, Gln127, Ser139, Asp295, Arg298, and Gln299. Gln127 being common to the mentioned studies and to our analysis may be considered as effective residue for allosteric inhibition thus depicting the accuracy of allosteric site selection in the present study (El-Baba et al 2020 ). Iftikhar et al in their in-silico study on inhibitors against three potential enzyme targets of SARS-CoV-2 reported Bagrosin as an allosteric inhibitor, binding with an energy of − 7.9 kcal/mol at an allosteric site lying close to the site reported in the present study, of SARS-CoV-2 proteinase with Lys5 as common interacting residue (Iftikhar et al 2020 ).…”
Section: Resultsmentioning
confidence: 67%
“…Work of Robinson and Vakonakis 193 focused on the protease M encoded by the SARS-COV-2 RNA genome. Its role is to process several of the virus structural proteins.…”
Section: Mass Spectrometry In the Era Of Covid-19mentioning
confidence: 99%
“…Elastic network model analysis, binding site predictions followed by MD simulations has been used to predict the allosteric sites on the main protease protein [ 118 , 119 ]. The identification of allosteric binding sites on the main protease has also been identified by mass spectrometry based studies [ 120 ]. The binding of small molecules on these sites is proposed to reduce the rate of substrate processing and dimerization.…”
Section: Overview Of Some Of the Applications Of Structural Bioinformmentioning
confidence: 99%